1984
DOI: 10.1021/jf00124a010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of diclofop-methyl in root-treated wheat and oat seedlings

Abstract: Diclofop-methyl [methyl 2-[4-(2,4-dichlorophenoxy)phenoxy]propanoate] was hydrolyzed initially to diclofop [ 2-[4-(2,4-dichlorophenoxy)phenoxy]propanoic acid] in roots of resistant wheat and susceptible oat. Diclofop was detoxified rapidly in wheat roots by aryl hydroxylation of the 2,4dichlorophenyl moiety to at least three isomeric aryl-hydroxylated compounds and conjugation to acidic aryl 0-glycosides. Virtually no diclofop accumulated in wheat roots, but in oat roots, approximately 35% of the radioactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…In corn the radioactivity detected as diclofop increased substantially following hydrolysis (Table IV). This indicated that in corn roots DM was metabolized predominantly to water-soluble ester conjugates similar to the glucose ester conjugates identified previously (12). The results did not differ greatly between corn roots treated with DM alone or in combination with 2,4-D (Table IV).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…In corn the radioactivity detected as diclofop increased substantially following hydrolysis (Table IV). This indicated that in corn roots DM was metabolized predominantly to water-soluble ester conjugates similar to the glucose ester conjugates identified previously (12). The results did not differ greatly between corn roots treated with DM alone or in combination with 2,4-D (Table IV).…”
supporting
confidence: 78%
“…Diclofop may be conjugated as a glucose ester (12) or ringhydroxylated (2,4-dichlorophenyl-OH) and conjugated as a phenolic conjugate (22). These water-soluble conjugates in tissue extracts may be quantified by HCI hydrolysis and subsequent quantification of diclofop and ring-OH diclofop as hydrolysis products (Tables IV, V).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In both plants diclofop-methyl is rapidly hydrolyzed to the free acid by esterases present in the cell free space or in the cytoplasm. The acid may be conjugated to an inactive bound form (glucose ester) or detoxified by aryl glucoside formation (14,23). The lipid solubility of both the ester and the acid allow them to partition into the membrane phase where the acid-base dissociation characteristics (pKa = 3.57) (15), the pH gradient, and the charge difference across the membrane causes diclofop to function as a proton ionophore.…”
Section: Discussionmentioning
confidence: 99%
“…In both susceptible oats and resistant wheat, diclofop-methyl is rapidly hydrolized to the free acid, diclofop (24442',4'-dichlorophenoxy)phenoxy)propanoic acid. In wheat diclofop is subsequently metabolized by aryl hydroxylation and conjugation to form an acidic, aryl-glucoside; in oat, diclofop is metabolized to a neutral glucosyl ester (7,14,21,23 ofdiclofop-methyl is less well understood than is the metabolism. In susceptible plants such as oat, diclofop-methyl induced an inhibition of leaf, stem, and root elongation, chlorosis of leaves (11), and severe damage to cellular ultrastructure (2).…”
mentioning
confidence: 99%